Impact of Grade I obesity on respiratory mechanics during video laparoscopic surgery - Orlandira Costa Araujo; Eloisa Bonetti Espada; Fernanda Magalhães Arantes Costa; Julia Araujo Vigiato; Maria José Carvalho Carmona; José Pinhata Otoch; João Manoel Silva, Jr.; Milton de Arruda Martins (Brazilian Journal of Anesthesiology, 2020)
Introduction and objectives: The association pneumoperitoneum and obesity in video laparoscopy can contribute to pulmonary complications, but has not been well defined in specific groups of obese individuals. We assessed the effects of pneumoperitoneum in respiratory mechanics in Grade I obese compared to non-obese. Methods: Prospective study including 20 patients submitted to video laparoscopic cholecystectomy, normal spirometry, divided into non-obese (BMI ≤ 25 kg.m-2) and obese (BMI > 30 kg.mg-2), excluding Grade II and III obese. We measured pulmonary ventilation mechanics data before pneumoperitoneum (baseline), and five, fifteen and thirty minutes after peritoneal insufflation, and fifteen minutes after disinflation (final). Results: Mean BMI of non-obese was 22.72 ± 1.43 kg.m-2 and of the obese 31.78 ± 1.09 kg.m-2, p <  0.01. Duration of anesthesia and of peritoneal insufflation was similar between groups. Baseline pulmonary compliance (Crs) of the obese (38.3 ± 8.3 mL.cm H2O-1) was lower than of the non-obese (47.4 ± 5.7 mL.cm H2O-1), p =  0.01. After insufflation, Crs decreased in both groups and remained even lower in the obese at all moments assessed (GLM p <  0.01). Respiratory system peak pressure and plateau pressure were higher in the obese, albeit variations were similar at moments analyzed (GLM p >  0.05). The same occurred with elastic pressure, higher in the obese at all times (GLM p =  0.04), and resistive pressure showed differences in variations between groups during pneumoperitoneum (GLM p =  0,05). Conclusions: Grade I obese presented more changes in pulmonary mechanics than the non-obese during video laparoscopies and the fact requires mechanical ventilation-related care. Resumo: Justificativa e objetivos: Em videolaparoscopias, a associação de pneumoperitônio e obesidade pode contribuir para complicações pulmonares, mas não está bem definida em grupos específicos de obesos. Avaliamos os efeitos do pneumoperitônio na mecânica respiratória dos obesos Grau I em comparação aos não obesos. Métodos: Estudo prospectivo envolvendo 20 pacientes submetidos à colecistectomia videolaparoscópica, com espirometria normal, separados em não-obesos (IMC ≤ 25 kg.m-2) e obesos (IMC > 30 kg.mg-2, excluídos obesos Grau II e III. Mensuramos dados da mecânica ventilatória pulmonar antes do pneumoperitônio basal, após cinco, quinze e trinta minutos da insuflação peritoneal e quinze minutos após a desinsuflação final. Resultados: O IMC médio dos não obesos foi de 22,72 ± 1,43 kg.m-2 e dos obesos 31,78 ± 1,09 kg.m-2, p <  0,01. A duração da anestesia e da insuflação peritoneal foram semelhantes entre os grupos. A complacência pulmonar (Crs) basal dos obesos (38,3 ± 8,3 mL.cm H2O-1) foi inferior aos não obesos (47,4 ± 5,7 mL.cm H2O-1), p =  0,01. Após a insuflação, a Crs diminuiu nos dois grupos e permaneceu ainda mais baixa nos obesos em todos os momentos avaliados (GLM p <  0,01). A pressão de pico e a pressão de platô do sistema respiratório foram mais elevadas nos obesos, mas apresentaram semelhantes variações nos momentos analisados (GLM p >  0,05). O mesmo ocorreu com a pressão elástica, mais elevada nos obesos em todos tempos (GLM p =  0,04), e a pressão resistiva apresentou diferenças nas variações entre os grupos durante o pneumoperitônio (GLM p =  0,05). Conclusão: Obesos Grau I apresentam maiores alterações na mecânica pulmonar que os não obesos em videolaparoscopias e este fato recomenda cuidados relacionados a ventilação mecânica.